Good Governance and Anti-Corruption: Responsibility to Protect Universal Health Care in Indonesia - Juwita, Ratna (Hasanuddin University, 2018)
The establishment of universal health care marks a new momentum for the progressive realization of the right to health in Indonesia. The problem of corruption in health sector endangers the sustainability of effective and quality health care, therefore, Indonesia established an anti-fraud system to protect the universal health insurance fund. This research seeks to analyze the current anti-fraud system in universal health insurance through the lens of international law and principles of good governance. The sociolegal approach is chosen to study the relationship between the State party obligations to international law and the implementation of international law concerning universal health care and anti-corruption in the designated anti-fraud system. Good governance principles are essential in designing an effective anti-fraud system due to the correlation between human rights and anti-corruption that both areas emphasize good governance principles as guiding principles for the realization of human rights and the making of potent anti-corruption strategy.